Analysis of Personal Competency of Educators in Increasing Advantage of Taruna Students - Dhian Supardam; Hadi Prayitno; Ayub Wimatra (STAI Hubbulwathan Duri, 2021)
This study seeks to identify the personality competencies possessed by aviation polytechnic educators in an effort to foster cadet excellence. This study is qualitative with a case study design and uses three data collection methods: in-depth interviews, participant observation, and documentation studies. The subjects of the study were educators from the Medan Aviation Polytechnic who were selected using a technique of purposive sampling. These are the findings of this study: Educators participate in self-improvement trainings in order to increase their contribution to cadet excellence. The personality competencies of educators are also reflected in the openness with which they carry out their respective responsibilities and duties. Educators' self-discipline in addressing problems related to their primary responsibilities demonstrates their personality competence in order to foster cadet excellence.